EXPLORING EFFICACY OF INFANT FEEDING TUBE AS A LOW COST ALTERNATIVE TO STENTING IN LOWER URETERIC STONE MANAGEMENT - Patil, Basavesh S.; Patil, Siddanagouda B.; Patil, Santosh R.; Kundargi, Vinay S.; Vaidya, Manoj K. (Eastern Ukrainian Medical Journal, 2025)
Introduction. Routine DJ stenting following URSL (Ureteroscopic Lithotripsy) is associated with irritative voiding symptoms, pain, UTI and requires additional hospital visit for stent removal. Externally draining ureteric catheters and stents with strings for easy self-removal have been used to overcome these drawbacks, but a cost effective and practical solution is yet to be found. Aim of this study is to evaluate the efficacy of placing an infant feeding tube (IFT) in lower ureter for 24 hours following URSL for lower ureteric stones in overcoming the stent related morbidity and avoiding a subsequent cystoscopy for stent removal. Methods. A prospective randomised study was conducted wherein 110 patients undergoing URSL for lower ureteric stones were randomised into 2 equal groups such that routine DJ (Double J) stenting using a 5Fr 26 cm DJ stent was done in group 1 and a 5Fr infant feeding tube mounted on a 0.032 inch guidewire was placed in the lower ureter and drained externally in the remaining 55 patients. Results. The average stone size in the DJ stent vs IFT group was 7.6 mm and 8.2 mm. Patients in the DJ stent group had a higher analgesic requirement (30% vs 23.6%). Irritative voiding symptoms 35 (63.6%) vs 4 (7.2%) [P=0.000]; hematuria 6 (10.9%) vs 1 (1.81%) [P=0.012] and fever 11 (20%) vs 4 (7.2%) [P=0.0047] were all significantly less in the IFT group. Conclusions. Use of infant feeding tube to drain the lower ureter will significantly reduce irritative voiding symptoms, hematuria and fever associated with usage of DJ stents while avoiding the need for any secondary procedures like DJ stent removal.